SERVICE QUALITY ASSESSMENT OF E-SAMBAT APPLICATION USING E-GOVQUAL DIMENSION APPROACH: A Case Study of Communication and Informatics Office Pasuruan - Meitasari, Bella Tri; Milad, Mohammad Khusnu; Permadi, Andhy (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
Technological developments facilitate state and regional authorities in providing public services through web and smartphone applications called e-Goverment. This application is also applied by the Communication and Informatics Service Pasuruan, that is the application of e-Sambat for its community. This research aims to provide an understanding of the quality of e-Sambat services based on the e-GovQual dimension approach, to find out the gap between e-Sambat service quality and the community's expectations in using the app properly, and to determine which items will be prioritized for immediate improvement in the e-Sambat app. This research method used a quantitative method with a descriptive approach that used questionnaires and books as research instruments. The method used to analyze the feasibility of applications using GAP and the Important Performance Analysis (IPA) method is used to analyze items that are prioritized for improvement. There were 445 respondents in this research. Based on the research results, the service quality of the e-Sambat app is highly feasible with a feasibility percentage value of 100%; the GAP of application performance and community expectations for the ease of use variable is 0.08; the trust variable is -0.04; the functionality of the interaction environment variable is 0.02; the reliability variable is -0.03; the content and appearance of information variable is 0.01; and the citizen support variable is 0.00. The overall average gap is 0.01, which means that the public is satisfied with the e-Sambat application service. There are six items that are prioritized for improvement, such as TR 1 (security of e-Sambat users' personal data), TR 6 (access control of e-Sambat users), RLB 1 (speed in downloading the e-Sambat form), CAI 7 (use of colors in the e-Sambat application), CAI 8 (graphics in the e-Sambat application), and CS 5 (user questions are responded quickly).